Faktor Risiko Kejadian Covid-19 Di Rumah Sakit Umum Daerah Andi Djemma Masamba - Fitriani, Aisyah Al; Fatmah Afrianty Gobel; Mansur Sididi; Nur Ulmy Mahmud; Sartika (Window of Public Health Journal, 2025)
Coronaviruses are a large family of viruses that cause mild to severe symptoms. On April 4, 2020, the WHO reported that the number of confirmed positive cases of COVID-19 was 1,056,157 people, with a death toll of 57,130 people. The purpose of this study is to determine the risk factors for the occurrence of COVID-19 at the Andi Djemma Masamba Regional General Hospital in 2021. The type of qualitative research is the case-control study method. The design of this study was carried out by first identifying the group of cases (COVID-19 sufferers) and then looking retrospectively at whether or not there are risk factors that are suspected to play a role. The sample in this study consisted of 352 respondents from Lewenshow's calculation, with a ratio of 1:3, consisting of 88 cases and 264 controls. The analysis used univariate and bivariate analyses with a chi-square correlation test. The results of this study show that age is a protective factor of the incidence of Covid-19 at Andi Djemma Masamba Hospital (OR=0.614; 95%CI=0.312-1.210), gender is a protective factor of the incidence of Covid-19 at Andi Djemma Masamba Hospital (OR=0.463; 95% CI=0.282-0.760), clinical symptoms are a protective factor of the incidence of Covid-19 at Andi Djemma Masamba Hospital (OR=0.020; 95% CI=0.119-0.808), and commobid which is a protective factor of the incidence of Covid-19 at Andi Djemma Masamba Hospital (OR=0.945; 95% CI=0.553-1). 616). The conclusion of this study shows that age, gender, clinical symptoms, and comorbidities are protective factors against the incidence of COVID-19. As a suggestion in this study, it is hoped that people with comorbidities will be able to control their comorbidities, considering that comorbidities are one of the factors that aggravate the incidence of COVID-19.